Game analysis of the knowledge sharing mechanism for the supply chain collaborative innovation - Liang Liu; Guo Chen; Xiaoge Niu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: In information economy era, innovation is the key to improve the competitiveness of enterprises. The traditional way of enterprise innovation is outdated and supply chain collaborative innovation has becoming popular. This paper aims to analyses the mechanism of knowledge sharing between enterprises in supply chain collaborative innovation. Design/methodology/approach: This paper analyzes the supply chain members' willingness to share knowledge by using the game theory. And the result of knowledge sharing between two companies is analyzed by using the evolutionary game. Findings: We broke the knowledge sharing process in supply chain collaborative innovation into knowledge mining and knowledge transferring. We got the best knowledge sharing strategy of each supply chain member. We gave the influencing factors of knowledge sharing between members for the knowledge sharing mechanisms in supply chain collaborative innovation. Research limitations/implications: We didn't study the willingness of more than two supply chain members to share knowledge and the result of knowledge sharing between them. And this situation is more realistic. Practical implications: Our findings can help to improve the effect of knowledge sharing in supply chain collaborative innovation. Originality/value: The paper introduces the game theory to knowledge sharing between members in supply chain collaborative innovation, deepens the understanding of knowledge sharing in supply chain collaborative innovation, and gives some interesting findings.
Keywords: 650; game theory; knowledge sharing; collaborative innovation; supply chain